Perfil da produção científica brasileira sobre papéis ocupacionais - FARIAS, Nicole Stefany de Oliveira Salgado (2023)
Introduction: Occupational roles are associated with human behavior, social expectations produced in a certain reality, and contribute to the perception of personal identity, also the organization and use of time. Changes in occupational roles are frequent in everyday life and impact on the lives of the public addressed by occupational therapy. Therefore, occupational therapists, both nationally and internationally, have produced knowledge about this subject to subsidize their interventions. In the Brazilian context, these studies are still scarce. Objective: This study aimed to describe the profile of the research done by Brazilian occupational therapists on occupational roles. Methodological Procedures: This is a literature review, with a quantitative and descriptive approach. The collection of information was performed through the search for scientific articles published in national occupational therapy journals and a database from a mapping of the bibliographic production produced by Brazilian post-graduate occupational therapists. Results/Discussion: A total of 26 articles, published in 12 different journals, were found. A higher frequency of research articles with a quantitative, cross-sectional and descriptive approach was observed. Concerning the population, the prevalence of female subjects in the adult and elderly age groups was identified, with some functionality compromise. Final Considerations: Knowing the profile of Brazilian publications on occupational roles enable to understand the research strategies adopted, the publics addressed and the main contributions to the field of occupational therapy.